2018
DOI: 10.1080/13548506.2018.1500023
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of cancer-related cognitive impairment, its impact on daily life and care received for it following treatment for breast cancer

Abstract: Several women who undergo treatment for breast cancer experience cancer-related cognitive impairment [CRCI] commonly known as 'Chemobrain' or 'Chemofog'. However, many oncologists and other cancer clinicians are unaware of the high prevalence and severity of these symptoms. Few qualitative studies on the topic provide a comprehensive description of this phenomenon. This study provides a detailed description of women's experiences of CRCI, its impact on daily life and care received for it following treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 43 publications
3
41
2
Order By: Relevance
“…Although memory was the most frequent cognitive change theme, multiple themes were identified and these often co‐occurred. The types of problems reported were consistent with those found in other qualitative studies . The co‐occurring cognitive problems suggest screening, assessment, and management approaches for cancer survivors should incorporate domains beyond memory and attention.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although memory was the most frequent cognitive change theme, multiple themes were identified and these often co‐occurred. The types of problems reported were consistent with those found in other qualitative studies . The co‐occurring cognitive problems suggest screening, assessment, and management approaches for cancer survivors should incorporate domains beyond memory and attention.…”
Section: Discussionsupporting
confidence: 81%
“…Systematic reviews or meta‐synthesis of qualitative studies and other individual qualitative studies with smaller numbers of breast cancer survivors have reported similar findings. For example, semistructured interviews with 18 breast cancer survivors, followed by a focus group, revealed that participants reported problems with short‐term memory, word finding, concentration, and poorer performance in work, study, driving, and financial management .…”
Section: Introductionmentioning
confidence: 58%
“…Among available treatment options, CT is most frequently linked to mild to moderate cognitive decline, as illustrated by commonly used terms as “chemobrain” or “chemofog” 3–6 . Cognitive impairment and associated poor quality of life (QOL) is rated as one of the most bothersome symptoms by cancer survivors and has long been reported during and after treatment courses 7–9 . In turn, poor QOL and increased levels of distress are related to increased use of health care and costs 10 .…”
Section: Introductionmentioning
confidence: 99%
“…These struggles become particularly pertinent when returning to work (Rimke et al, 2018). To date, there is limited research into the psychosocial impact of chemobrain (Bolton and Isaacs, 2018) and the lack of prior information, validation or understanding from healthcare professionals, friends and family, has led to reports of disempowerment and subsequently receiving minimal levels of emotional and professional support (Mitchell and Turton, 2011).…”
mentioning
confidence: 99%